(untitled) (Itinera, 2023)
Part I A new art for a new world Martin Heidegger and Barnett Newman Stefano Esengrini stefano.esengrini@unicatt.it François Fédier’s contribution to the understanding of Martin Heidegger’s thought represents the point from which we start to clarify the meaning of the path taken by the philosopher after Being and Time. The phenomenon of Ereignis as Enowning thus constitutes the horizon within which the possibility occurs for man to encounter his world and take root in it as if he were at home. The need to overcome the crisis that threatens the Western world determines the possibility of experiencing the world in a new way and founding new knowledge capable of giving a measure to our existence on earth. From this perspective, America becomes the place that knows how to symbolically embody the possibility that man has of establishing an authentic relationship with his surroundings and of developing a knowledge that is in tune with this opportunity. Part II Based on the rethinking of the metaphysical essence of art, we will be able to interpret the work of Barnett Newman as an attempt to give form in painting to the thought of a new start. More specifically, the prominence assumed by color becomes the index of the need to give shape to the space and time within which the world occurs. Thanks to the secret symmetry that exists between Newman and the work of Henry David Thoreau, we will thus be able to clarify the nature of the contribution provided by American art to the determination of a new world that America, more radically than other places on earth, has been able to articulate in unheard of forms capable of projecting a new hope for Western man today and for the future that is destined for us.